STUDY OF THE BODY VALUES IN THE CONTEXT OF THE NEW MASTER PROGRAMS. A COMPARATIVE ANALYSIS OF THE STUDENTS FROM THREE MASTER PROGRAMS OF PHYSICAL EDUCATION AND SPORT FACULTY CLUJ-NAPOCA - Iosif SANDOR; Ioan Virgil GANEA; Emanuele ISIDORI; Adrian PASCAN; Gabriela Virginia RUSU (Cluj University Press, 2015)
With the establishment of new Master programs, the option of students includes a wide range which reflects, in most cases, some tangible values. When choose follow the Masters program, not all students are aware, not all of them take it into account. The Magister students came from different social, cultural and geographical backgrounds. Their basic body values have different aspects like a social, cultural and geographical reflection. Those reflections differ from one society to another from one individual to another. The type of body values dominant in Romanian society are mostly those which are connected to the hedonistic, esthetic and emotional dimension of the body itself. Therefore, our study aims to prioritize and emphasize those values that Master students of the Faculty of Physical Education and Sport of the Babes-Bolyai University in Cluj-Napoca are endowed as part of their studies in order to facilitate their integration into social life, highlighted by the changes of modern society post EU accession. Studiu privind valorile corporale în contextul noilor programe Masterale. Analiza comparativă a studenților din cadrul a trei programe Master a Facultății de Educație Fizică și Sport din Cluj-Napoca. Odată cu înființarea noilor programe Masterale, opțiunea studenților cuprinde o paletă largă ce reflectă, în majoritatea cazurilor, anumite valori corporale de care, în momentul alegerii programului masteral de urmat, nu toți studenții sunt conștienți și de care nu toți țin cont. Studenții masteranzi provin din medii sociale și geografice diferite în care valorile corporale capătă aspecte diferite, de la o societate la alta de la un individ la altul. În general, în România, tipologia valorilor umane este asociată cu dimensiunile hedonistice, estetice și emoționale ale corpului uman. Tocmai de aceea, studiul nostru are ca obiectiv să ierarhizeze și să scoată în evidență acele valori cu care studenții masteranzi ai Facultății de Educație Fizică și Sport ai Universității Babeș-Bolyai din Cluj-Napoca sunt înzestrați ca parte integrantă a formării caracterului lor ce le va facilita integrarea în structurile vieții sociale puse sub influența transformărilor societății moderne post aderare la Uniunea Europeană.  Cuvinte Cheie: studenți, master, programe, educație